An observation on sludge granulation in an enhanced biological phosphorus removal process - Ong, Y.H.; Chua, A.S.; Lee, B.P.; Ngoh, G.C.; Hashim, M.A. (1061-4303, 2012)
A sequencing batch reactor (SBR) seeded with flocculated sludge and fed with synthetic wastewater was operated for an enhanced biological phosphorus removal (EBPR) process. Eight weeks after reactor startup, sludge granules were observed. The granules had a diameter of 0.5 to 3.0 mm and were brownish in color and spherical or ellipsoidal in shape. No significant change was observed in sludge granule size when operational pH was changed from 7 to 8. The 208-day continuous operation of the SBR showed that sludge granules were stably maintained with a sludge volume index (SVI) between 30 to 55 mL/g while securing a removal efficiency of 83% for carbon and 97% for phosphorus. Fluorescent in situ hybridization (FISH) confirmed the enrichment of polyphosphate accumulating organisms (PAOs) in the SBR. The observations of sludge granulation in this study encourage further studies in the development of granules-based EBPR process.